Metoda wartości uzyskanej jako kluczowy element opartego na wiedzy zarządzania złożonymi przedsięwzięciami informatycznymi - Dyczkowski, Mirosław (The Earned Value Method as a One of the Fundamentals of the Knowledge Based IT Project Management Concept, 2005)
The article presents possibilities of application of the Earned Value (EV) method as an element of knowledge based IT project management system. In the first part the author briefly characterizes the integrated approach to IT project - management. The next section contains the description of EVA/EVM concept and its application in IT project management. In the third part the author explains the idea of implementation EVA/EVM system as a tool of knowledge acquisition and management in IT projects. The finally section contains few conclusions - the most important is that the EV method can be one of the fundamentals of knowledge based project management (KBPM) concept.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1081, s. 258-268